Some perspectives on general policies, special policies, and superior policies in science, technology, and innovation in Vietnam - Hoang Lan Chi; Hoang Xuan Long (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
The system of science, technology, and innovation (STI) policies can be categorized into general, specific, and advanced policies. Each type has its characteristics, significance, and content. The analysis of general, specific, and advanced policies allows a clearer understanding of the current situation and development solutions for STI policies in Vietnam in the near future. Code: 23112301